Development of a feasible and acceptable digital prehabilitation pathway to improve elective surgical outcomes - Linedale, Ecushla C.; Bills, Eleanor; Dimopoulos, Anastasia; Yeoh, Jackie; Nolan, Mandy; Hume, Vicki; Coles, Sharyn; Andrews, Jane M. (Frontiers in Digital Health, 2023)
Objective(s): To codesign and assess the feasibility, acceptability, and appropriateness of a hospital-initiated, community delivered approach to health optimization (prehab) prior to planned surgery. Design: Participatory co-design combined with a prospective, observational cohort study (April-July 2022). Setting: A large metropolitan tertiary referral service with 2 participating hospitals Participants: All people referred for orthopaedic assessment for joint replacement surgery (hip or knee) triaged as category 2 or 3. Exclusions: Category 1; no mobile number. Response rate 80%. Intervention: My Prehab Program is a digitally enabled pathway that screens participants for modifiable risk factors for post-operative complications and provides tailored information to enable health optimization prior to surgery with the help of their regular doctor. Outcome measures: Acceptability, feasibility, appropriateness, and engagement with the program. Results: 36/45 (80%) registered for the program (ages 45-85 yrs.), completed the health-screening survey and had ≥1 modifiable risk factor. 18 responded to the consumer experience questionnaire: 11 had already seen or scheduled an appointment with their General Practitioner and 5 planned to. 10 had commenced prehab and, 7 planned to. Half indicated they were likely (n=7) or very likely (n=2) to recommend My PreHab to others. The My PreHab Program scored an average 3.4 (SD 0.78) for acceptability, 3.5 (SD 0.62) for appropriateness, and 3.6 (SD 0.61) for feasibility, out of a score of 5. Conclusion(s): This digitally delivered intervention is acceptable, appropriate, and feasible to support a hospital-initiated, community-based prehab program.